Frontiers in agronomy - Frontiers Research Foundation (Frontiers Media S.A, 2019)
Frontiers in Agronomy is a multidisciplinary open access platform dedicated to the dissemination of transdisciplinary research and the publishing of rigorously high-impact research on all topics related to agronomy. This emcompasses topics such as weed management, pest management, cropping practices, disease management, plant-soil Interactions, automation in agricultural systems, organic and biological farming, and post-harvest treatment and storage, with further specialty sections in developement to host all aspects of the world of agronomy.
Keywords: Agronomy : Periodicals; Agriculture : Periodicals; Agriculture; Agronomy